Christmas tale - Stilton, Geronimo (New York Scholastic Publication, 2005)
Celebrate the holidays in style mouse-style, that is! Join Geronimo for his first-ever special edition. It was Christmas time on Mouse Island and I couldn't wait to celebrate with my friends and family. But then I discovered that they were all traveling out of town for the holidays and I'd be spending Christmas alone! I was starting to feel like a real Grinch. Would this be my loneliest Christmas ever
Keywords: English Tale-Children; Christmas Tales